Validação da técnica de LAMP para diagnóstico de Influenza e SARS-CoV-2 e avaliação epidemiológica em um campus universitário - Gabriel Pissolati Mattos Bretz (2023)
Respiratory viruses are a major cause of mortality worldwide. SARS-CoV-2 has been linked to 6,8 million deaths as of March 2023, and it is estimated that the Influenza virus is responsible for up to 50,000 deaths per year. The etiological diagnosis in this case is important to identify outbreaks and intervening in the transmission of viruses, but the nonspecificity of clinical signs is a complicating factor. A laboratorial diagnosis, fast and accessible to the various complexities of the health system, can help to combat the impacts of respiratory viruses. With the objective of carrying out an epidemiological evaluation of the SARS-CoV-2, Influenza A and Influenza B viruses in 2022 in the community served by the MONITORACOVID UFMG program, LAMP reactions in nasopharyngeal swab samples were validated and standardized, being performed simultaneously in the same equipment with constant temperature of 65°C, reaction time of 30 minutes and visual reading. The study showed analytical characteristics comparable to known results in RT-qPCR (gold standard) in the same samples. For SARS-CoV-2, 50 samples were tested and obtained a sensitivity of 84.0%, specificity of 100% and a Kappa index of 0.84; for Influenza A, 52 samples were tested, resulting in sensitivity of 85.2%, specificity of 100%, and Kappa index 0.85. The sensitivity of LAMP reactions for SARS-CoV-2 and Influenza A has been shown to be lower in samples with Ct > 31 in RT-qPCR. For the Influenza B reaction, 26 samples were tested, 25 of which were known to be undetectable, one detectable, and 100% concordance of the results was obtained. For the epidemiological evaluation, 243 samples of symptomatic patients from the UFMG community were tested, equivalent to 10% of the monthly number assisted by the program. The annual positivity rate for SARS-CoV-2 was 28.7%, for Influenza A: 1.6%, Influenza B: 0.0%. There were found Indeterminate results for SARS-CoV-2 and Influenza A (0.8% each), 1.2% of invalid results and 66.9% of the samples tested negative for the three viruses. The standardized assay was able to assess the epidemiology of respiratory viruses in the studied population with results comparable to those found in the literature.